Theoretical Approaches to Leadership in the Indian Oil and Gas Sector: Optimizing Safety and Productivity for Energy Security in the Indian Oil and Gas Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper discusses the leadership issues and its significance with reference to oil and gas sector in India. It stresses on the fact that the oil and gas leaders have to deal with important responsibility of optimizing safety and productivity so that the all-time high demand of oil and gas can be met. It presents oil and gas sector landscape in brief and stresses on the fact that effective leadership at all levels in oil and gas organisations can help achieve the goal of 100% energy security. The paper discusses the sector specific work environment and urges to have manpower having expertise in the oil and gas domain so as to meet the unconventional challenges along with the conventional ones. An individual on entry in an organisation goes through various development stages. An effective leader will analyse the development stage the subordinate is in and match his leadership style to his stage for performing required tasks and duties (i.e. partnering for performance).